A cognitive interpretation of thermograhic images using novel fuzzy learning semantic memories - Wong, Kenneth Yang Fei. (2010)
In March 2003, a severe respiratory disease have broke out in Singapore causing a total of 238 infected and 33 died, implying a fatality rate of 14%. One of the measures put in place to prevent the spread of the disease in Singapore is the employment of thermograph cameras at access points of Singapore to screen people going in and out of Singapore for fever conditions. This report looks into the technology of thermography from its basis to how it is widely used in medical fields to aid in early diagnosis of diseases like breast cancer.